Diversitas Serangga Hutan Tanah Gambut Di Palangkaraya Kalimantan Tengah - Tambunan, Julian; Ginantra, I Ketut; Watiniasih, Ni Luh (Metamorfosa: Journal of Biological Sciences, 2019)
This study aims to determine the diversity of insects and plants used as a habitat in unburned and previously burned peat land forests in Palangkaraya, Central Kalimantan. Insects were collected by beating the branches of plants, aerial sweeping, pitfall traps and light traps. Plants were identified in situ or plant samples were collected and identified later in the Lab. The diversity of insects were compared between unburned and previously burned peat forests by analyzing its index diversity (H’) and index of similarity (IS). In total, the insects collected from unburned peat forest were 551 individual, belongs to 12 order and 51 families, and 431 individual insects were collected from previously burned peat forest which belongs to 10 order and 38 families. The family of insects that most frequently found at both areas was Formicidae (Hymenoptera). The insects diversity of both forests were still high, that is H' = 3,45 of unburned peat forest and H '= 3,11 of previously burned peat forest, with the similarity index IS > 50% of both peat forests. The number of plant species found was higher in unburned peat forest (38 species) than in previously burned peat forest (9 species).  The previously burned forest was dominated by Acacia plants, while in unburned peat forest the plants seem to evenly spread.